Pengenalan "Hand Soap dan Hand Sanitizer Gel" Berbasis Algae Kepada Pembudidaya Rumput Laut di Teluk Ekas untuk Mencegah Penyebaran Covid-19 pada Tatanan Kehidupan Baru - Haji Sunarpi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
The covid-19 pandemic changed the order of human life in the world, including in Indonesia. In an effort to prevent the spread of covid-19 to a new life order, it is necessary to make efforts to adjust the social order of life. Having a clean lifestyle, such as washing hands with soap and sterilizing hands in addition to wearing masks, is a culture that must be nurtured in the community, including seaweed cultivators. Many researchers report that seaweed contains antibacterial, anticancer, anti-UV and antiviral properties, in addition to phytohormones and hydrocolloid compounds, such as carrageenan, agar and alginates. Therefore, seaweed is a potential marine biota to be developed into liquid soap (hand soap) and hand sanitizer. This article reports on the introduction and training of seaweed-based liquid and sanitary soap in Ekas Bay, East Lombok Regency. The target of this service is seaweed cultivators, so that in the waiting period for the seaweed harvest, there are activities that can produce products to prevent the spread of Covid-19 and increase the income of coastal communities. Keywords: seaweed, liquid soap, hand sanitary ware, covid-19